Occupational safety and health practice: a study for wastewater treatment - Md Sah, Mohamad Sahril; Mohd Said, Mohamad Luqman Hakim; Khalid, Amir; Jaat, Norrizam; Ishak, Izuan Amin; Zainal Abidin, Shaiful Fadzil (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is a discipline with broad scope involving many specialized fields. In other words, occupational health and safety encompasses the social, mental, and physical. This study focuses on the sustainability of the river by having wastewater treatment at the Kenny Leather (M) Sdn. Bhd. The waste management sector is an important employment sector. However, workers in the waste management sector are faced with various risks. They are exposed to risks such as manual handling (manipulating waste), working postures (standing), vibrations (driving vehicles, work equipment), chemical substances, biological agents, work organization (pace of work, job control), mechanical hazards (cuts, bruises). The data collection was carried out through site investigation using HIRARC form and interview with the worker in the factory as the methodology. The objective of this study is to promote the occupational environment adaptable to enhance the sustainability of the environment especially water and promote the safety to the employer and employees at the workplace based on the existing potential hazard. This study was encouraged to implement alternative options such as cleaner production, waste minimization and waste re-utilisation in order to waste pollution. The 5-M model were used to identify the causes of the crane error in five major parts man, machine, medium, management and mission. Then, the Fault Tree Analysis described and elaborated in more details about the content in 5-M model. All parties with full support of Malaysia government should play major roles and responsibilities by making sure that appropriate safety practices are carried out to minimize the accident rates at the workplace and have strategies and measures need to be taken toward an effective management of water resources, pollution control and prevention of environmental degradation.